Proceeding - Coopertaive Learning Method Type Numbered Head Together (NHT) Student in Efforts to Increase Liverliness Mastery in Economics Faculty Muhammadiyah University of North Sumatera - Nel Arianty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Proceeding - Coopertaive Learning Method Type Numbered Head Together (NHT) Student in Efforts to Increase Liverliness Mastery in Economics Faculty Muhammadiyah University of North Sumatera